PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 1 BATHIN SOLAPAN KECAMATAN BATHIN SOLAPAN - Anidawati Anidawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the problem of the low learning outcomes of students in Civics learning in SD Negeri 1 BathinSolapan. The purpose of this study was to improve the learning process and improve the learning outcomes of Civics in the fifthgrade students of SD Negeri 1 Bathin Solapan in the 2017/2018 academic year through the application of numbered headstogethers. The study was conducted in two cycles, one cycle was carried out twice as much as the research action. The researchsubjects were 24 V students consisting of 13 male students and 11 female students. This research was conducted in the evensemester of 2017/2018 school year in February 2018. Data collection techniques included observation sheets and test sheetsduring the action and documentation of learning activities. Civics learning outcomes in cycle I obtained an average of 72.11 andcycle II with an average of 77.65. It can be concluded that with the application of the numbered heads together model it canimprove the learning outcomes of Civics in the fifth grade students of SD Negeri 1 Bathin Solapan. This is evident from theincrease in the average student learning outcomes 77.65 a significant increase in cycle II. This success is supported by thereadiness of the teacher in designing learning and the learning process implemented according to plan.